1983
DOI: 10.1002/neu.480140105
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal elements in snail tentacles as revealed by horseradish peroxidase backfilling

Abstract: The snail tentacle ganglion is a prominent structure that innervates an epithelial pad sensitive to wind and odors. Its neural composition, and that of the sensory pad, was studied in the terrestrial snail Achatina fulica by applying horseradish peroxidase to the distal end of the cut tentactle nerve. Five types of neurons were labelled by the procedure: receptors, located in the subepithelial region; three kinds of interneurons, located in the ganglion and its digitlike extensions; and a bipolar neuron, locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…There are two major olfactory processing structures: the digitate ganglion at the superior tentacle tip right behind the nose (Ito et al, 2000) and the procerebral (PC) lobe in the CNS. The PC lobe receives both first-order input from olfactory receptors and second-order input from the digitate ganglion (Chase and Kamil, 1983;Murakami et al, 2004).…”
Section: A Comparative Perspectivementioning
confidence: 99%
“…There are two major olfactory processing structures: the digitate ganglion at the superior tentacle tip right behind the nose (Ito et al, 2000) and the procerebral (PC) lobe in the CNS. The PC lobe receives both first-order input from olfactory receptors and second-order input from the digitate ganglion (Chase and Kamil, 1983;Murakami et al, 2004).…”
Section: A Comparative Perspectivementioning
confidence: 99%
“…Four types of neurons have been studied in the digits and tentacular ganglion by backfilling tentacular nerves with horseradish peroxidase in a snail (Chase and Kamil, 1983) and with Lucifer yellow in L. marginatus (Ito et al, 2000). The four types of stained neurons were "sensory neurons", "gamma cells", "ganglion cells", and "lateral cells".…”
Section: Gabaergic Neurons In the Primary Olfactory System And Cnsmentioning
confidence: 99%
“…The digits ramify from the apical part of the tentacular ganglion into many thin neuropils and connect the neuropil region with the sensory epithelium. The surface of the digits is covered with a number of neuronal cell bodies including olfactory receptor neurons and olfactory interneurons (Chase and Kamil, 1983;Chase and Tolloczko, 1993;Ito et al ., 2000). The digits can be divided into three major groups (right, central, and left groups), and two of them (left and right groups) have cell clusters, termed the cell masses, at their bases (Ito et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no essential differences between the repertoires of the types of neurons in the superior and inferior tentacular ganglia (Chase and Kamil, 1983a;Chase and Kamil, 1983b;Ito et al, 2000), Ito et al found that there are four structural differences between the two pairs of tentacles by means of backfilling of the tentacular nerves: (1) fewer fibers form the thick fiber tracts in neuropils in the superior tentacles than in the inferior tentacles; (2) there are more stained neurons in the superior tentacles than in the inferior tentacles; (3) the ratio of stained neurons to total neurons is lower in the superior tentacles than in the inferior tentacles; and (4) as with the digits, the tentacular ganglion is partially covered by a single cell layer in the inferior tentacles whereas the superior tentacles lack such a cell layer.…”
Section: R Matsuo and Othersmentioning
confidence: 99%